Establishment of plasma microRNA detection method by using taqman probe based quantitative reverse transcription PCR - Wang, Y-N; Yu, L; Zhao, X-S; Zhang, W; Wan, J; Yu, B (Cellular and Molecular Biology, 2015)
copies in the PCR reaction. Our study provided a standardized quantification method for plasma miRNAs which might be used as biomarker in many diseases research.